Generative mechanisms of IT-enabled organisational performance in resource-constrained Emergency Medical Services organisations in South Africa - Buchana, Yasser (Department of Information Systems, 2019)
Problem Statement: Emergency medical services (EMS) organisations have one of the highest levels of dependence on and use of information technology (IT) to support delivery of emergency medical services. The need for EMS organisations to provide efficient and effective emergency medical services has emphasised the importance of performance management. Organisational performance which is monitored and evaluated through key performance indicators (KPIs) plays an important role in EMS organisations. Organisational performance helps to monitor, evaluate and communicate outcomes in the form of KPIs. Empirical evidence shows that quantitative KPIs have been designed with little in-depth understanding of the underlying IT usage mechanisms that influence organisational performance. Unfortunately, such quantitative KPI reports have been limited in explaining organisational performance underpinned by IT. Purpose / rationale of the research: The purpose of this research study was to identify the generative mechanisms associated with IT-enabled organisational performance and to explain how these mechanisms interact. In the context of resource-constrained EMS organisations, quantitatively defined KPIs are not suitable for explaining the underlying causes of performance variations and outcomes. The lack of empirical evidence on IT-enabled organisational performance as well as the lack of theoretical explanations of the underlying mechanisms provided the primary rationale for this study. In addition, this study sought to provide answers to the following research question: What generative mechanisms explain IT-enabled organisational performance in resource-constrained EMS organisations? Theoretical approach/methodology/design: This study was informed by the critical realist philosophy of science and used the complex adaptive systems theory together with institutional theory as the theoretical lenses to investigate the research question in a manner that jointly explained the generative mechanisms. Using interviews, participant observation, organisational performance data and documents collected from a single case study, the study used abduction and retroduction techniques to explicate the mechanisms of IT-enabled organisational performance. Findings: Findings indicate that the IT-enabled organisational performance mechanisms can be categorised into two types of generative mechanisms. These are structural and coordination mechanisms. The explanation of the mechanisms developed in this study take into consideration three important elements: (1) the technological, cultural and structural mechanisms that influence IT-enabled organisational performance; (2) the unpredictable, non-linear, adaptive nature of emergency medical services environments; and (3) the complexities that arise in the interactions between EMS organisations and their environments. Originality/contribution: In respect of IT-enabled organisational performance this study contributes to both organisational and health information systems literature by developing a multi-level research framework that is informed by the realist philosophical stance. The framework plays an explanatory role which relates to its inherent ability to offer explanatory insights into the necessary mechanisms that give rise to organisational performance. This framework has the potential to guide empirical research and provide theoretical explanations of different domains or disciplines that are concerned with identifying IT usage mechanisms which influence organisational performance. These include the significance of the coordination and structural mechanisms which, under differing conditions of uncertainty, produce variations in performance outcomes. Implications: Findings from this study can be integrated into broader emergency medical policy planning and health programme management. The model developed by the study provides a fresh understanding of the underpinning mechanisms enabling performance in resource-constrained EMS organisations. It can be used to assist emergency medical institutions and practitioners in South Africa and other sub-Saharan African countries, especially Southern African Development Community (SADC) countries to improve emergency medical service delivery to the public. The findings provide a guide for improving management of emergency medical situations and resources in their respective resource-constrained contexts. Furthermore, findings from the study can also guide improved design and implementation strategies and policies of EMS systems initiatives in South Africa and sub-Saharan developing countries.